Polishing pad with reduced defects and method of manufacturing semiconductor device using same
By adjusting the composition and renovation conditions of the polished polishing layer, combined with ultraviolet light irradiation, the defects and scratch problems caused by debris in the CMP process are solved, and the more efficient polishing performance and higher finished product rate are achieved.
Patent Information
- Application Number
- CN202411010872.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-06
- Filing Date
- 2024-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
In a chemical mechanical polishing (CMP) process, friction between the polishing surface and the semiconductor substrate or debris generated during the cutting of the diamond disc leads to defects and scratches on the polishing surface.
By adjusting the proportion of polyurethane prefabrication, foaming agent and curing agent in the polishing layer, and renovation under specific conditions, such as 93rpm at the pressure disk, 9LBS of the renovator, the renovator speed to the renovator to the speed of the renovator to the speed of the renoor to the velocity of the renovation device to the speed of the renovation device to the speed of the renovation device to the speed. Under the conditions of 64rpm and scanning speeds of 19 times/minute, combined with ultraviolet light irradiation, the debris particle size and potential difference of the polishing layer are adjusted.
To maximize the occurrence of defects and scratches in the CMP process, while maintaining the excellent physical characteristics and performance of the pads, improve the performance and finished product rate of CMP.
Smart Images

Figure CN119369287A_ABST
Abstract
Description
Technical Field
[0001] Embodiments relate to a polishing pad having reduced defects and scratches in a chemical mechanical polishing (CMP) process and a method of making a semiconductor device using the same. Background Art
[0002] Chemical mechanical polishing (CMP) in the semiconductor manufacturing process is a step in which a semiconductor substrate (such as a wafer) is fixed to a head and brought into contact with the surface of a polishing pad mounted on a platen, and then, while the platen and the head are moving relative to each other, the semiconductor substrate is chemically treated by supplying slurry, thereby mechanically polishing the bumps and depressions on the surface of the semiconductor substrate.
[0003] The polishing pad is an essential component that plays an important role in this CMP process. Generally, the polishing pad is composed of a polyurethane resin and has grooves on its surface for a large flow of slurry and pores for supporting its fine flow.
[0004] When preparing the polishing pad, diisocyanate reacts with polyol to obtain a prepolymer, which is then mixed with a curing agent and a foaming agent and cured to obtain a polyurethane foam sheet. Then, the upper and lower surfaces of the polyurethane foam sheet are cut into a desired thickness to obtain an upper pad, a groove of a specific shape is formed on the surface of the upper pad using a tip or the like, and then it is bonded to the polyurethane lower pad to make a polishing pad.
[0005] In the process of preparing semiconductor devices, the CMP process can be performed multiple times. The semiconductor device includes multiple layers, each of which includes a complex and fine circuit pattern. In addition, in recent years, the size of a single chip of a semiconductor device has been reduced, and the pattern of each layer is developing in a more complex and finer direction. Therefore, in the process of preparing semiconductor devices, the purpose of the CMP process has been expanded to not only planarize circuit wiring, but also to separate circuit wiring and improve the wiring surface, etc. Therefore, more advanced and reliable CMP performance is required.
[0006] In a CMP process using such a polishing pad, debris is generated due to friction between the polishing surface and the semiconductor substrate, or when the polishing surface is cut by a diamond disk for conditioning.
[0007] Prior art documents
[0008] (Patent Document 1) Korean Patent Publication No. 2016-0027075. Summary of the invention
[0009] Technical issues
[0010] In the CMP process using a polishing pad, debris is formed due to friction between the polishing surface and the semiconductor substrate or when the polishing surface is cut by a diamond disk for conditioning. In the CMP process, these debris cause defects and scratches on the polishing surface.
[0011] Accordingly, the inventors' research results found that the size and potential difference characteristics of the debris obtained from the polishing pad have an impact on the generation of defects; and, when the above characteristics are adjusted to a certain range, the occurrence of defects and scratches in the CMP process can be minimized while maintaining the excellent physical properties and performance of the polishing pad.
[0012] Furthermore, the inventors' research results have found that when ultraviolet light is used in the CMP process, a polishing pad with reduced debris particle size can be achieved, and the occurrence of defects and scratches in semiconductor devices can be minimized by irradiating ultraviolet light in the CMP process based on these characteristics of the polishing pad.
[0013] Therefore, embodiments are directed to a polishing pad with reduced defects and a method of manufacturing a semiconductor device using the same.
[0014] Technical Solution
[0015] According to an embodiment, a polishing pad is provided, which includes a polishing layer, wherein the polishing layer includes a polyurethane-based prepolymer, a foaming agent and a curing agent; under the conditions of a platen speed of 93 rpm, a dresser load of 9 lbs, a dresser speed of 64 rpm, and a scanning speed of 19 times / minute, the polishing layer is dressed for 10 minutes, and deionized water is supplied at a rate of 300 cc / minute, and the obtained debris D50 particle size is less than 50 μm, and the pH is 5.5; when the pH is 5.5, the potential difference of the aqueous solution containing 0.01% by weight of the debris is -20 mv to 30 mv.
[0016] According to another embodiment, a polishing pad is provided, which includes a polishing layer containing a polyurethane resin, wherein when a cerium dioxide slurry is supplied at a rate of 250 ml / min at a platen speed of 93 rpm, a dresser load of 9 lbs, a dresser speed of 64 rpm, and a scanning speed of 19 times / min, the polishing layer is dressed, and then irradiated with ultraviolet light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, the resulting debris satisfies the following relationship (1).
[0017] D50 [0 min] > D50 [4 min] ... (1)
[0018] Here, D50[4min] is the D50 particle size of the chips obtained in the conditioning before irradiation with ultraviolet light, and D50[4min] is the D50 particle size of the chips obtained when irradiated with ultraviolet light for 4 minutes after conditioning.
[0019] According to another embodiment, there is provided a method for preparing a semiconductor device, which includes polishing a surface of a semiconductor substrate using the polishing pad.
[0020] According to another embodiment, a method for preparing a semiconductor device is provided, which includes conditioning a polishing layer of a polishing pad under irradiation of ultraviolet light having a wavelength of 100 nm to 380 nm while chemically and mechanically polishing a semiconductor substrate using the polishing pad.
[0021] Advantageous Effects of the Invention
[0022] In the polishing pad according to the present embodiment, the chip size and potential difference characteristics obtained therefrom are adjusted to a specific range. Therefore, in the CMP process, the occurrence of defects and scratches can be minimized while maintaining the excellent physical properties and performance of the polishing pad.
[0023] The polishing pad according to the present embodiment has the characteristic that the particle size of debris is reduced when ultraviolet light is irradiated in the CMP process. Therefore, by utilizing these characteristics of the polishing pad, the occurrence of defects and scratches in the semiconductor device can be minimized by irradiating ultraviolet light in the CMP process. In addition, since the polishing pad according to the embodiment has excellent characteristics such as polishing rate, when the semiconductor device is manufactured using the polishing pad, the performance and yield of CMP can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A process for preparing a semiconductor device using a polishing pad according to one embodiment is shown.
[0025] Figure 2 The occurrence of defects caused by debris in the process of manufacturing semiconductor devices is shown.
[0026] Figure 3 A method of measuring the particle size of debris obtained from the polishing pad according to the embodiment is shown.
[0027] Figure 4 A method of measuring the potential difference of a chip aqueous solution obtained from a polishing pad according to an embodiment is shown.
[0028] Figure 5 and Figure 6 Changes in the particle size of chips obtained from the polishing pads according to the examples and the comparative examples with respect to the ultraviolet irradiation time are respectively shown.
[0029] Figure 7and Figure 8 A configuration of an apparatus for irradiating ultraviolet light during a CMP process according to an embodiment is shown. DETAILED DESCRIPTION
[0030] Hereinafter, various embodiments and examples will be described in detail with reference to the accompanying drawings.
[0031] In the following description of the embodiment, when it is determined that the description may make the subject matter of the embodiment unclear, the detailed description of the known functions and configurations contained herein will be omitted. In addition, for the sake of convenience of explanation, the size of each component in the drawings may be exaggerated or omitted, and they may be different from the actual size.
[0032] In this specification, when a component is described as being formed on / under another component or connected or coupled to each other, it covers the case where these components are formed, connected or coupled directly or indirectly through another component. In addition, it should be understood that the criteria of the terms on and under each component may vary depending on the direction in which the object is viewed.
[0033] In this specification, the terms referring to the various components are used to distinguish them from each other, and are not intended to limit the scope of the embodiments. In addition, in this specification, unless otherwise specified in the context, singular expressions are interpreted as also covering the plural.
[0034] Throughout this specification, the terms first, second, etc. are used to describe various components. However, these components should not be limited by these terms. The purpose of using these terms is to distinguish one element from another element.
[0035] In this specification, the term "comprising" is intended to specify specific features, regions, steps, processes, elements and / or components. It does not exclude the existence or addition of any other features, regions, steps, processes, elements and / or components unless there is a clear description to the contrary.
[0036] The molecular weight of the compound or polymer described in this specification, such as the number average molecular weight or the weight average molecular weight, is based on the well-known relative mass of carbon- 12. Although its unit is not described, it can be understood as the same numerical value of molar mass (g / mol) when necessary.
[0037] In the numerical ranges of limiting component sizes, physical properties, etc. described in this specification, when a numerical range limited only by an upper limit and a numerical range limited only by a lower limit are respectively exemplified, it should be understood that the numerical range combining these upper and lower limits is also included in the exemplary range of the present invention.
[0038] Chemical Mechanical Polishing
[0039] Semiconductor devices are prepared by chemical and mechanical polishing with polishing pads.
[0040] A method of manufacturing a semiconductor device according to an embodiment includes polishing a surface of a semiconductor substrate using a polishing pad.
[0041] Specifically, the method of preparing a semiconductor device may include providing a polishing pad according to an embodiment; and polishing a surface of a semiconductor substrate by relatively rotating a polishing surface of a polishing layer in contact with the surface of the semiconductor substrate.
[0042] Figure 1 A process for preparing a semiconductor device using a polishing pad according to an embodiment is shown. Figure 1 Once the polishing pad (100) according to the embodiment is attached to the platen (200), a semiconductor substrate (600) as an object to be polished is set on the polishing pad (100). In this case, the surface of the semiconductor substrate (600) to be polished is in direct contact with the polishing surface of the polishing pad (100). The polishing slurry (450) can be sprayed onto the polishing pad through a nozzle for polishing. The flow rate of the polishing slurry (450) supplied through the nozzle can be adjusted according to the target at about 10 cm / s. 3 / min to about 1,000cm 3 / minute. For example, it can be about 50cm 3 / min to about 500cm 3 / minute, but not limited to this.
[0043] Thereafter, the semiconductor substrate (600) and the polishing pad (100) are rotated relative to each other, thereby polishing the surface of the semiconductor substrate (600). In this case, the rotation direction of the semiconductor substrate (600) and the rotation direction of the polishing pad (100) may be the same direction or opposite directions. The rotation speeds of the semiconductor substrate (600) and the polishing pad (100) may be respectively selected in the range of about 10 rpm to about 500 rpm according to the target. For example, it may be about 30 rpm to about 200 rpm, but is not limited thereto.
[0044] The semiconductor substrate (600) mounted on the polishing head (510) is pressed against the polishing surface of the polishing pad (100) with a predetermined load to contact the polishing surface, and then the surface thereof can be polished. The load applied by the polishing head (510) to the polishing surface of the polishing pad (100) and the surface of the semiconductor substrate (600) can be between about 1 gf / cm2 according to the target. 2 To about 1000gf / cm 2 For example, it can be about 10 gf / cm 2 To about 800gf / cm 2 , but not limited to this.
[0045] In one embodiment, the semiconductor substrate (600) as the object to be polished may include an oxide layer, a tungsten layer or a composite layer thereof. Specifically, the semiconductor substrate (600) may include an oxide layer, a tungsten layer or a composite layer of an oxide layer and a tungsten layer. The composite layer of the oxide layer and the tungsten layer may be a multilayer film in which a tungsten layer is stacked on one side of the oxide layer, or may be a single layer film in which an oxide region and a tungsten region are mixed in a single layer. Since the object to be polished has such a film material and the polishing pad has the characteristics according to this embodiment at the same time, the semiconductor device manufactured according to the method for manufacturing a semiconductor device may have minimal defects.
[0046] In one embodiment, the method for preparing a semiconductor device may further include: in the step of polishing the object to be polished, providing any one of a slurry for polishing an oxide layer and a slurry for polishing a tungsten layer. Alternatively, the slurry for polishing an oxide layer and the slurry for polishing a tungsten layer are sequentially supplied to the polishing surface.
[0047] For example, if the semiconductor substrate as the object to be polished includes an oxide layer, the method for preparing a semiconductor device may include providing a slurry for polishing the oxide layer. If the semiconductor substrate includes a tungsten layer, the method for preparing a semiconductor device may include providing a slurry for polishing the tungsten layer. If the semiconductor substrate includes a composite layer of an oxide layer and a tungsten layer, the method for preparing a semiconductor device may include sequentially providing a slurry for polishing the oxide layer and a slurry for polishing the tungsten layer to the polishing surface. Here, depending on the process, a slurry for polishing the oxide layer may be provided first, and then a slurry for polishing the tungsten layer may be provided, or a slurry for polishing the tungsten layer may be provided first, and then a slurry for polishing the oxide layer may be provided.
[0048] In one embodiment, in order to maintain the polishing surface of the polishing pad (100) in a state suitable for polishing, the method for preparing a semiconductor device may further include treating the polishing surface of the polishing pad (100) with a dresser (300) while polishing the semiconductor substrate (600).
[0049] In the polishing pad according to the embodiment, the particle size and potential difference characteristics of the debris obtained from its polishing layer are adjusted to a specific range. Therefore, in the CMP process, the occurrence of defects and scratches can be minimized while maintaining the excellent physical properties and performance of the polishing pad. Thus, semiconductor devices with excellent quality can be efficiently manufactured using the polishing pad.
[0050] Polishing pad
[0051] The polishing pad according to the embodiment includes a polishing layer. Specifically, the polishing pad includes a polishing layer including a polyurethane resin.
[0052] Specifically, the polishing pad includes a polishing layer and a support layer. In addition, an adhesive layer may be inserted between the polishing layer and the support layer.
[0053] Figure 2 The occurrence of defects caused by debris in the process of manufacturing semiconductor devices is shown. Figure 2 , defects (650) or scratches on the surface of the semiconductor device formed by debris (150) from the polishing layer. According to an embodiment, the particle size and potential difference of the debris from the polishing layer can be adjusted to a specific range to minimize the occurrence of defects or scratches.
[0054] In the polishing pad according to the embodiment, chips obtained therefrom have a particle size within a specific range.
[0055] Figure 3 A method of measuring the particle size of debris obtained from a polishing pad according to an embodiment is shown. Figure 3 , a polishing pad is mounted on a platen of a CMP polishing machine, and the polishing layer is conditioned while providing deionized water, and the debris of the polishing layer formed after 10 minutes of conditioning is collected in the form of a solution mixed with deionized water. The pH of the debris aqueous solution is adjusted using an aqueous nitric acid solution or an aqueous potassium hydroxide solution, and then the particle size of the debris is measured using a particle size analyzer.
[0056] Specifically, the debris can be obtained by providing 300cc / min of deionized water during conditioning of the polishing layer of the polishing pad at a platen speed of 93rpm, a dresser load of 9lbs, a dresser speed of 64rpm, and a scanning speed of 19 times / min. The particle size of the debris can be an average particle size, i.e., a D50 particle size. As a specific example, a diamond disk (e.g., a CI45 type disk from Saesol) with a pad cutting rate (PCR) of 80μm / hr to 90μm / hr can be used in the dresser.
[0057] According to one embodiment, under the condition of pH 5.5, the D50 particle size of the chips obtained during the conditioning of the polishing layer for 10 minutes is less than 50 μm.
[0058] Specifically, at a pH of 5.5, the D50 particle size of the chips obtained when the polishing layer is dressed for 10 minutes under the above conditions can be 40 μm or less, 30 μm or less, 25 μm or less, 22 μm or less, 20 μm or less, 19 μm or less, 18 μm or less, or 17 μm or less, and 5 μm or more, 10 μm or more, or 15 μm or more.
[0059] More specifically, at a pH of 5.5, the D50 particle size of the chips obtained when the polishing layer is conditioned for 10 minutes under the above conditions can be 10 μm to 50 μm, 10 μm to 40 μm, 10 μm to 30 μm, 10 μm to 25 μm, 10 μm to 22 μm, 10 μm to 21 μm, 10 μm to 20 μm, 10 μm to 19 μm, 10 μm to 18 μm or 10 μm to 17 μm.
[0060] According to another embodiment, at a pH of 10, the D50 particle size of the chips obtained during conditioning of the polishing layer for 10 minutes is below 35 μm.
[0061] Specifically, at a pH of 10, the D50 particle size of the chips obtained when the polishing layer is dressed for 10 minutes under the above conditions can be 35 μm or less, 30 μm or less, 25 μm or less, 24 μm or less, 23 μm or less, 22.3 μm or less, 22 μm or less, or 21 μm or less, and 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more.
[0062] More specifically, at a pH of 10, the D50 particle size of the chips obtained when the polishing layer is conditioned for 10 minutes under the above conditions can be 15 μm to 35 μm, 15 μm to 30 μm, 15 μm to 25 μm, 15 μm to 24 μm, 15 μm to 23 μm, 15 μm to 22.3 μm, 15 μm to 22 μm or 15 μm to 21 μm.
[0063] According to a specific embodiment, the D50 particle size of the chips obtained during the conditioning of the polishing layer may be 25 μm or less at a pH of 5.5 and 22.3 μm or less at a pH of 10.
[0064] Within the above preferred range, the occurrence of defects and scratches during the CMP process can be minimized while maintaining the excellent physical properties and performance of the polishing pad.
[0065] Furthermore, in the polishing pad according to the embodiment, the chip aqueous solution obtained therefrom may have a potential difference within a specific range.
[0066] Figure 4 A method of measuring the potential difference of a chip aqueous solution obtained from a polishing pad according to an embodiment is shown. Figure 4, a polishing pad is mounted on the platen of the CMP polisher, and the polishing layer is trimmed while providing deionized water, and the debris of the polishing layer formed after 10 minutes of trimming is collected in the form of a solution mixed with deionized water. In order to ensure the stability of particles in the debris aqueous solution, it is kept at room temperature for 24 hours to precipitate particles with a particle size of 20 μm or more. Then, the upper clear liquid within 10 mm from the top surface of the solution is taken as a sample. Then, the pH of the sample is adjusted using an aqueous nitric acid solution or an aqueous potassium hydroxide solution, and then the potential difference of the sample is measured using a potential difference analyzer. The sample may contain debris at a weight concentration of 0.01%.
[0067] As an example, at a pH of 5.5, the potential difference of an aqueous solution containing 0.01% weight concentration of debris obtained when the polishing layer is conditioned for 10 minutes under the above conditions can be above -20mv, above -15mv, above -10mv, above -5mv, above 0mv, above 5mv, above 10mv, below 50mv, below 40mv, below 30mv, below 20mv, below 15mv, or below 10mv.
[0068] According to one embodiment, at a pH of 5.5, the potential difference of an aqueous solution containing 0.01% by weight of debris obtained when the polishing layer is conditioned for 10 minutes under the above conditions is -20 mv to 30 mv.
[0069] Specifically, at a pH of 5.5, the potential difference of an aqueous solution containing 0.01% weight concentration of debris obtained when the polishing layer is conditioned under the above conditions for 10 minutes can be -15mV to 25mV, -10mV to 25mV, 10mv to 20mv, -10mv to 15mv, -5mv to 30mv or 0mv to 30mv.
[0070] More specifically, the potential difference of the aqueous solution of the debris may be positive (+).
[0071] In the above preferred range, the potential difference of the debris is similar to the potential difference of the polishing particles (e.g., cerium particles) in the CMP polishing composition (slurry); therefore, the occurrence of defects can be further reduced. Specifically, the potential difference is a quantitative representation of the magnitude of the repulsive and attractive forces between the particles caused by the positive and negative ions of the particles in the suspension. If the potential difference of the debris and the polishing particles is similar, the repulsive force between the particles increases, thereby preventing the particles from aggregating; therefore, the occurrence of defects and scratches can be reduced by reducing the particle size in the composition.
[0072] As another example, at a pH of 10, the potential difference of an aqueous solution containing 0.01% weight concentration of debris obtained when the polishing layer is conditioned for 10 minutes under the above conditions may be above -50 mv, above -45 mv, above -40 mv, above -35 mv, or above -30 mv, and below 30 mv, below 20 mv, below 10 mv, below 0 mv, below -10 mv, or below -20 mv.
[0073] Specifically, at a pH of 10, the potential difference of an aqueous solution containing 0.01% by weight of debris obtained when the polishing layer is conditioned for 10 minutes under the above conditions may be -50 mv to -10 mv.
[0074] More specifically, at a pH of 10, the potential difference of an aqueous solution containing 0.01% weight concentration of debris obtained when the polishing layer is conditioned for 10 minutes under the above conditions can be -50 mv to -15 mv, -50 mv to -20 mv, -50 mv to -25 mv, -40 mv to -10 mv or -30 mv to -10 mv.
[0075] Furthermore, since the polishing pad has a certain relationship between the particle size of debris and the potential difference according to the pH condition, the above-mentioned effect can be further enhanced.
[0076] According to an embodiment, the value of the following formula (1) may be -20 μm / mV to 30 μm / mV. In a specific embodiment, it may be -10 μm / mV to 20 μm / mV.
[0077] D50[5.5] / Zp[5.5]...(1)
[0078] Wherein, D50[5.5] is the chip particle size D50 (μm) obtained when the polishing layer is conditioned at a pH of 5.5, and Zp[5.5] is the potential difference (mV) of an aqueous solution containing 0.01% by weight of chips obtained when the polishing layer is conditioned at a pH of 5.5.
[0079] For example, the value of formula (1) may be greater than -20 μm / mV, greater than -10 μm / mV, greater than -5 μm / mV, greater than 0 μm / mV, less than 30 μm / mV, less than 20 μm / mV, less than 15 μm / mV, less than 10 μm / mV, or less than 5 μm / mV. Specifically, the value of formula (1) may be -10 μm / mV to 15 μm / mV, -5 μm / mV to 20 μm / mV, -5 μm / mV to 15 μm / mV, 0 μm / mV to 15 μm / mV, -5 μm / mV to 10 μm / mV, 0 μm / mV to 10 μm / mV, -5 μm / mV to 5 μm / mV, or 0 μm / mV to 5 μm / mV.
[0080] According to another embodiment, the value of the following formula (2) may be 60% to 120%. In a specific embodiment, it may be 70% to 110%.
[0081] (D50[5.5] / D50
[10] )×100...(2)
[0082] Wherein, D50[5.5] is the particle size D50(50) of the debris obtained by trimming the polishing layer at a pH of 5.5, and D50
[10] is the particle size D50(50) of the debris obtained by trimming the polishing layer at a pH of 10.
[0083] For example, the value of formula (2) may be 60% or more, 70% or more, 75% or more, and 120% or less, 110% or less, 105% or less, 100% or less, 95% or less, 90% or less, 85% or less, or 80% or less. Specifically, the value of formula (2) may be 70% to 105%, 70% to 100%, 70% to 95%, 70% to 90%, 70% to 85%, or 75% to 85%.
[0084] According to another embodiment, the value of the following formula (3) may be 25 mv to 65 mv. In a specific embodiment, it may be 35.5 mv to 60 mv.
[0085] Zp[5.5]–Zp
[10] ...(3)
[0086] Wherein, Zp[5.5] is the potential difference (mV) of an aqueous solution containing 0.01% by weight of debris obtained by conditioning the polishing layer at a pH of 5.5, and Zp
[10] is the potential difference (mV) of an aqueous solution containing 0.01% by weight of debris obtained by conditioning the polishing layer at a pH of 10.
[0087] For example, the value of formula (3) can be 25mv or more, 35.5mv or more, 36mv or more, and 65mv or less, 60mv or less, 55mv or less, 50mv or less, or 45mv or less. Specifically, the value of formula (3) can be 35.5mv to 55mv, 35.5mv to 50mv, 35.5mv to 45mv, 35.5mv to 40mv, 36mv to 60mv, 36mv to 50mv, 36mv to 45mv, or 36mv to 40mv.
[0088] In addition, the polishing pad according to the embodiment has excellent performance and overall physical properties.
[0089] For example, when a ceria slurry is used to polish a silicon oxide layer of a silicon wafer using a polishing pad, the polishing speed (removal rate) can be / minute or more, / minute or more, / minute or more / minute or more, and / minute or less, / minute or less, / minute or less / min or less.
[0090] As a specific example, when a silicon oxide layer of a silicon wafer is polished using a polishing pad with a ceria slurry, the polishing speed according to the following mathematical formula 1 may be 2200 to 2500. / minute.
[0091] [Mathematical formula 1]
[0092]
[0093] Specifically, the polishing speed may be the polishing speed of a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. In addition, the polishing speed may be measured under a polishing load of 4.0 psi while the polishing pad is rotated at a speed of 150 rpm, the calcined cerium oxide slurry is provided to the polishing pad at a speed of 250 ml / min, and the platen is rotated at a speed of 150 rpm for 60 seconds. The temperature conditions when measuring the polishing speed are not particularly limited, and may be, for example, room temperature conditions.
[0094] In addition, the pad cut rate of the polishing layer may be 30 μm / hr to 60 μm / hr, 30 μm / hr to 50 μm / hr, 40 μm / hr to 60 μm / hr, or 40 μm / hr to 50 μm / hr.
[0095] The thickness of the polishing pad may be 0.8 mm to 5.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.1 mm. Within the above range, the basic physical properties of the polishing pad can be fully exerted while minimizing the particle size deviation between the upper and lower parts.
[0096] Polishing pad behavior under UV light
[0097] The polishing pad according to an embodiment has the characteristic that the particle size of debris is reduced when ultraviolet light is irradiated during the CMP process. Therefore, by utilizing these characteristics of the polishing pad, the occurrence of defects and scratches in semiconductor devices can be minimized by irradiating ultraviolet light during the CMP process.
[0098] Figure 5 and Figure 6 Changes in the particle size of chips obtained from the polishing pads according to the examples and the comparative examples with respect to the ultraviolet irradiation time are respectively shown.
[0099] Reference Figure 5 , for the polishing pad according to an embodiment, the particle size of the debris decreases with the passage of ultraviolet light irradiation time, and it is measured to be the smallest at 2 to 4 minutes. Thereafter, when the ultraviolet light irradiation time is further extended to 6 to 8 minutes, it shows a slightly increasing trend. In general, the particle size of the debris tends to decrease with the passage of ultraviolet light irradiation time. On the other hand, the polishing pad according to the comparative example shows a tendency that the particle size of the debris generally increases with the passage of ultraviolet light irradiation time. It is measured that it is almost doubled after 10 minutes compared to the initial stage.
[0100] When irradiated with UV light, the molecular bonds break and the particles aggregate. It is speculated that the particle size of the debris tends to increase or decrease depending on which of the two is dominant. This trend may depend on the composition and characteristics of the polishing pad.
[0101] In order to measure the particle size of the debris, the polishing pad was attached to the platen of the CMP polishing machine, the polishing layer was conditioned while the CMP slurry was supplied, and the polishing layer debris formed after 10 minutes of conditioning was collected in the form of a solution mixed with the CMP slurry. Thereafter, the debris solution was irradiated with ultraviolet light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from an appropriate distance, and then the particle size of the debris was measured using a particle size analyzer.
[0102] Specifically, the debris can be obtained by providing 250 ml / min of ceria slurry during the dressing of the polishing layer at a platen speed of 93 rpm, a dresser load of 9 lbs, a dresser speed of 64 rpm, and a scan rate of 19 times / min. The particle size of the debris can be an average particle size, i.e., a D50 particle size. As a specific example, a diamond disk (e.g., a CI45 type disk from Saesol) with a pad wear rate (PWR) of 80 μm / hr to 90 μm / hr can be used in the dresser.
[0103] In a polishing pad according to one embodiment, when the polishing layer is dressed under the conditions of a platen speed of 93 rpm, a dresser load of 9 lbs, a regulator speed of 64 rpm, and a scanning speed of 19 times / min, while providing cerium dioxide slurry at 250 ml / min, and then irradiating ultraviolet light with a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, the resulting debris satisfies the following relationship (1).
[0104] D50[0min]>D50[4min]...(1)
[0105] Here, D50[0min] is the D50 particle size of the chips obtained in the conditioning before irradiation with ultraviolet light, and D50[4min] is the D50 particle size of the chips obtained when irradiated with ultraviolet light for 4 minutes after conditioning.
[0106] Specifically, the difference between D50[0min] and D50[4min] in relational expression (1) may be a certain level or higher. For example, when ΔD50[0-4min] calculated according to the following formula is 5 μm or more, it is more advantageous in terms of the debris reduction effect due to ultraviolet irradiation.
[0107] ΔD50[0-4min]=D50[0min]-D50[4min]
[0108] Here, D50[0min] is the D50 particle size of the chips obtained in the conditioning before irradiation with ultraviolet light, and D50[4min] is the D50 particle size of the chips obtained when irradiated with ultraviolet light for 4 minutes after conditioning.
[0109] Specifically, ΔD50[0-4min] may be 5 μm or more, 7 μm or more, 10 μm or more, or 13 μm or more, and 35 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. More specifically, ΔD50[0-4min] may be 5 μm to 30 μm, 5 μm to 25 μm, 10 μm to 30 μm, or 10 μm to 25 μm.
[0110] For example, D50[4min] may be 40 μm or less, 35 μm or less, 30 μm or less, 27 μm or less, or 25 μm or less, and may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. As a specific example, D50[4min] may be 30 μm or less. As a more specific example, D50[4min] may be 5 μm to 30 μm. Within the above preferred range, the occurrence of defects in semiconductor devices due to debris may be further minimized.
[0111] For example, D50[0min] may be 20 μm or more, 25 μm or more, 30 μm or more, or 35 μm or more, and 65 μm or less, 60 μm or less, 55 μm or less, or 45 μm or less. Specifically, D50[0min] may be 20 to 60 μm or 30 to 50 μm.
[0112] More specifically, D50[0 min] may be 35 μm or more, and D50[4 min] may be 30 μm or less.
[0113] According to another embodiment, the polishing pad may satisfy the following equation 2:
[0114] D50[4min] <D50[8min]...(2)
[0115] Among them, D50[4min] is the D50 particle size of the debris obtained by irradiating ultraviolet light for 4 minutes after repair, and D50[8min] is the D50 particle size of the debris obtained by irradiating ultraviolet light for 8 minutes after repair.
[0116] The difference between D50[8min] and D50[4min] in relation (2) may be a certain level or lower. For example, when ΔD50[8-4min] calculated according to the following formula is 20 μm or less, it is more conducive to maintaining the trend of reducing the particle size of the debris due to ultraviolet irradiation.
[0117] ΔD50[8-4min]=D50[8min]=D50[4min]
[0118] Among them, D50[4min] is the D50 particle size of the debris obtained by irradiating ultraviolet light for 4 minutes after repair, and D50[8min] is the D50 particle size of the debris obtained by irradiating ultraviolet light for 8 minutes after repair.
[0119] Specifically, ΔD50[8-4min] may be 20 μm or less, 15 μm or less, or 10 μm or less, and 3 μm or more, or 5 μm or more. More specifically, ΔD50[8-4min] may be 3 μm to 20 μm, 3 μm to 15 μm, 3 μm to 10 μm, or 5 μm to 15 μm.
[0120] For example, D50[8min] may be 55 μm or less, 50 μm or less, 45 μm or less, or 40 μm or less, and 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. Specifically, D50[8min] may be 20 μm to 50 μm or 25 μm to 40 μm.
[0121] More specifically, D50[8 min] may be 30 μm to 40 μm, and D50[4 min] may be 20 μm to 30 μm.
[0122] According to another embodiment, the polishing pad may satisfy the following equation 3:
[0123] (D90[0min]–D10[0min])>(D90[4min]–D10[4min])...(3)
[0124] Among them, D10[0min] and D90[0min] are the D10 and D90 particle sizes of the debris obtained by repairing before ultraviolet light irradiation, and D10[4min] and D90[4min] are the D10 and D90 particle sizes of the debris obtained by ultraviolet light irradiation for 4 minutes after repairing.
[0125] The difference between (D90[0 min]−D10[0 min]) and (D90[4 min]−D10[4 min]) in the relation (3) may be a certain level or higher.
[0126] For example, when ΔD90-10[4 min] calculated according to the following formula is 50 μm or more, it is more advantageous in terms of the chip size reduction effect due to ultraviolet irradiation.
[0127] ΔD90-10[4min]=(D90[0min]–D10[0min])–(D90[4min]–D10[4min])
[0128] Among them, D10[0min] and D90[0min] are the D10 and D90 particle sizes of the debris obtained by repairing before ultraviolet light irradiation, and D10[4min] and D90[4min] are the D10 and D90 particle sizes of the debris obtained by ultraviolet light irradiation for 4 minutes after repairing.
[0129] Specifically, ΔD90-10[4min] may be 50 μm or more, 70 μm or more, 100 μm or more, or 120 μm or more, and 300 μm or less, 250 μm or less, 200 μm or less, or 150 μm or less. More specifically, ΔD90-10[4min] may be 50 μm to 300 μm, 100 μm to 200 μm, or 100 μm to 150 μm.
[0130] (D90[0min]-D10[0min]) in the relational expression (3) may be 80 μm or more, 100 μm or more, 120 μm or more, or 140 μm or more, and 220 μm or less, 200 μm or less, or 180 μm or less. Specifically, (D90[0min]-D10[0min]) may be 100 μm to 200 μm or 140 μm to 180 μm.
[0131] (D90[4min]-D10[4min]) in the relation (3) may be 10 μm or more, 20 μm or more, or 30 μm or more, and 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. Specifically, (D90[4min]-D10[4min]) may be 20 to 60 μm or 30 to 50 μm.
[0132] Furthermore, the polishing pad according to an embodiment has excellent overall physical properties.
[0133] For example, when a silicon oxide layer of a silicon wafer is polished with a ceria slurry using a polishing pad, while irradiating with ultraviolet light of a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, the polishing speed (removal rate) can be / minute or more, / minute or more, / minute or more / minute or more, and / minute or less, / minute or less, / minute or less, / minute or less / min or less.
[0134] As a specific example, when a silicon oxide layer of a silicon wafer is polished with a ceria slurry using a polishing pad, and irradiated with ultraviolet light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, the polishing speed according to the following mathematical formula 1 can be / min to / minute.
[0135] [Mathematical formula 1]
[0136]
[0137] Specifically, the polishing speed may be the polishing speed of a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. In addition, the polishing speed may be measured under a polishing load of 4.0 psi while the polishing pad is rotated at a speed of 150 rpm, the calcined cerium oxide slurry is provided to the polishing pad at a speed of 250 ml / min, and the platen is rotated at a speed of 150 rpm for 60 seconds. The temperature conditions when measuring the polishing speed are not particularly limited, and may be, for example, room temperature conditions.
[0138] In addition, when the polishing pad is tested at a dressing pressure of 6 lbf and a rotation speed of 100 to 110 rpm, the pad wear rate (PWR) may be 15 μm / hr to 40 μm / hr. Specifically, the pad wear rate of the polishing layer may be 15 μm / hr to 35 μm / hr, 15 μm / hr to 30 μm / hr, 20 μm / hr to 40 μm / hr, or 15 μm / hr to 22 μm / hr.
[0139] The thickness of the polishing pad may be 0.8 mm to 5.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.1 mm. Within the above range, the basic physical properties of the polishing pad can be fully exerted while minimizing the particle size deviation between the upper and lower parts.
[0140] Polishing layer
[0141] The polishing layer provides a polishing surface that contacts the semiconductor substrate during the CMP process and constitutes a top pad in the polishing pad.
[0142] The polishing layer according to an embodiment includes a polyurethane resin.
[0143] The polishing layer includes a polyurethane-based prepolymer, a foaming agent, and a curing agent. Specifically, the polyurethane resin may be formed from a composition including a polyurethane-based prepolymer, a foaming agent, and a curing agent.
[0144] Specifically, the polishing layer includes a polyurethane-based resin, which is a reaction product of a polyurethane-based prepolymer, a blowing agent, and a curing agent, i.e., a cured product of a composition in which each component is mixed. More specifically, it includes a porous polyurethane-based resin. In addition, the polishing layer may include a plurality of pores formed by the blowing agent.
[0145] The thickness of the polishing layer can be, for example, 0.8 mm or more, 1 mm or more, 1.2 mm or more, or 1.5 mm or more, and 5 mm or less, 3 mm or less, 2.5 mm or less, or 2 mm or less. As a specific example, the thickness of the polishing layer can be 0.8 mm to 5 mm or 1.5 mm to 3 mm.
[0146] The density of the polishing layer can be, for example, 0.6 g / cm 3 Above, 0.7g / cm 3 Above or 0.75g / cm 3 Above, and 0.9g / cm 3 Below, 0.85g / cm 3 Below or 0.8g / cm 3 As a specific example, the density of the polishing layer can be 0.6 g / cm 3 Up to 0.9g / cm 3 or 0.7g / cm 3 Up to 0.9g / cm 3 .
[0147] The hardness of the polishing layer may be, for example, 30 Shore D or more, 40 Shore D or more, or 50 Shore D or more, and 80 Shore D or less, 70 Shore D or less, 65 Shore D or less, or 60 Shore D or less. As a specific example, the hardness of the polishing layer may be 30 Shore D to 80 Shore D or 50 Shore D to 65 Shore D.
[0148] The tensile strength of the polishing layer can be, for example, 5 N / mm 2 Above, 10N / mm 2 Above or 15N / mm 2 Above, and 30N / mm 2 Below, 25N / mm 2 Below or 20N / mm 2 As a specific example, the tensile strength of the polishing layer can be 5N / mm 2 Up to 30N / mm 2 or 15N / mm 2 Up to 25N / mm 2 .
[0149] The elongation of the polishing layer may be, for example, 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and 300% or less, 250% or less, 200% or less, or 150% or less. As a specific example, the elongation of the polishing layer may be 50% to 300% or 90% to 130%. The elongation may be the elongation at break.
[0150] As a specific example, the polishing layer may have a hardness of 50 to 65 Shore D, 15 N / mm 2 Up to 25N / mm 2 tensile strength and elongation of 90% to 130%.
[0151] The pores are dispersedly present in the polishing layer.
[0152] The average diameter of the pores may be, for example, 10 μm to 60 μm, 10 μm to 50 μm, 20 μm to 50 μm, 20 μm to 40 μm, 10 μm to 30 μm, 20 μm to 25 μm, or 30 μm to 50 μm.
[0153] In addition, the total area of the pores can be 30% to 60%, 35% to 50%, or 35% to 43% based on the total area of the polishing layer. In addition, the total volume of the pores can be 30% to 70% or 40 to 60% based on the total volume of the polishing layer.
[0154] The polishing layer may have grooves on its surface for mechanical polishing. The grooves may have a depth, width, and pitch required for mechanical polishing, which are not particularly limited.
[0155] In the polishing pad according to an embodiment, the polishing layer has a chlorine (Cl) content of 10000 ppm or less when analyzed according to the IEC 62321-3-2 standard.
[0156] Specifically, the chlorine content can be obtained by measuring the chlorine content in the sample using IEC 62321-3-2, which is an international standard for measuring specific substances in polymers by combustion ion chromatography (C-IC). In this case, the sample to be measured for chlorine content can be a circular sample having a size of 3 cm in diameter and 0.3 cm in height obtained from the polishing layer of the polishing pad.
[0157] The IEC 62321-3-2 standard is a test method for screening halogen components developed in accordance with halogen usage regulations. Compared with traditional halogen analysis methods (such as oxygen bomb-IC and oxygen bottle-IC), this test method has excellent precision / accuracy and reproducibility, and is automated; therefore, the reliability of the test results is excellent.
[0158] In a method for measuring the chlorine content in a polishing pad according to an embodiment, a sample containing an organic chlorine (C-Cl) component is loaded into a combustion tube and burned by an electric furnace. The resulting substance is transferred to an adsorption tube, and the amount of chloride ions (Cl-) is determined by ion chromatography.
[0159] In a polishing pad according to an embodiment, the chlorine content in the polishing layer may be 10000 ppm or less, for example, 5000 ppm or less, 1000 ppm or less, 500 ppm or less, 200 ppm or less, 100 ppm or less, 80 ppm or less, or 50 ppm or less. Since the chlorine content is adjusted to the above range, the particle size of the debris can be reduced while maintaining the excellent physical properties and performance of the polishing pad, thereby minimizing the occurrence of defects and scratches in the CMP process.
[0160] In addition, the lower limit of the range of the chlorine content in the polishing layer according to an embodiment may be, for example, 0 ppm or more, more than 0 ppm, 1 ppm or more, 5 ppm or more, 10 ppm or more, 20 ppm or more, 50 ppm or more, or 100 ppm or more. Within the above preferred range, when the debris is aggregated into a suitable size, the surface area and adsorption force can be adjusted to promote adsorption and desorption in the wafer and the polishing pad, and the polishing performance can be made more suitable by adjusting the electrical attraction / repulsion force.
[0161] As a specific example, when analyzed according to the IEC 62321-3-2 standard, the polishing layer has a chlorine (Cl) content of 10 ppm to 1000 ppm. As another specific example, when analyzed according to the IEC 62321-3-2 standard, the polishing layer has a chlorine (Cl) content of 10 ppm to 100 ppm, 20 ppm to 80 ppm, or 20 ppm to 50 ppm. As yet another specific example, when analyzed according to the IEC 62321-3-2 standard, the polishing layer has a chlorine (Cl) content of 50 ppm to 10000 ppm or 100 ppm to 10000 ppm.
[0162] As described above, since the polishing pad according to an embodiment has the chlorine content adjusted to a certain range, the size of debris can be reduced, thereby minimizing the occurrence of defects and scratches during the CMP process.
[0163] Polyurethane-based prepolymers
[0164] A polishing pad according to an embodiment includes a polyurethane-based prepolymer.
[0165] Prepolymers generally refer to polymers with a relatively low molecular weight in which the degree of polymerization is adjusted to an intermediate level so that they can be easily molded into shaped articles in the process of producing a cured product. Prepolymers can be formed into the final cured product alone or after reacting with another polymerizable compound.
[0166] In one embodiment, the polyurethane-based prepolymer may be prepared by reacting an isocyanate compound with a polyol.
[0167] The isocyanate compound used for preparing the polyurethane-based prepolymer may be one selected from aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate or a combination thereof.
[0168] The isocyanate compound may include, for example, one selected from toluene 2,4-diisocyanate (2,4-TDI), toluene 2,6-diisocyanate (2,6-TDI), naphthalene 1,5-diisocyanate, p-phenylene diisocyanate, diisocyanate, 4,4′-diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and combinations thereof.
[0169] The polyol is a compound containing at least two or more hydroxyl groups (-OH) per molecule, and may include, for example, one selected from polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, and combinations thereof.
[0170] The polyol may include, for example, one selected from polytetramethylene ether glycol, polypropylene glycol ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and combinations thereof.
[0171] The weight average molecular weight (Mw) of the polyol may be 100 to 3000. The polyol may have a weight average molecular weight (Mw), for example, of 100 to 3000, for example, 100 to 2000, for example, 100 to 1800.
[0172] In one embodiment, the polyol may include a low molecular weight polyol having a weight average molecular weight (Mw) of 100 to 300 and a high molecular weight polyol having a weight average molecular weight (Mw) of 300 to 1,800.
[0173] The weight average molecular weight (Mw) of the polyurethane-based prepolymer may be 500 to 3000. The polyurethane-based prepolymer may have a weight average molecular weight (Mw), for example, of 1000 to 2000, or for example, of 1000 to 1500.
[0174] In one embodiment, the isocyanate compound used to prepare the polyurethane-based prepolymer may include an aromatic diisocyanate compound, and the aromatic diisocyanate compound may include, for example, 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI). The polyol compound used to prepare the polyurethane-based prepolymer may include polytetramethyl ether glycol (PTMEG) and diethylene glycol (DEG).
[0175] In another embodiment, the isocyanate compound for preparing the polyurethane-based prepolymer may include an aromatic diisocyanate compound and an alicyclic diisocyanate compound. For example, the aromatic diisocyanate compound includes 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), and the alicyclic diisocyanate compound includes dicyclohexylmethane diisocyanate (H12MDI). The polyol compound for preparing the polyurethane-based prepolymer may include polytetramethyl ether glycol (PTMEG) and diethylene glycol (DEG).
[0176] The polyurethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 5% by weight or more, 8% by weight or more, or 10% by weight or more, and 13% by weight or less, 12% by weight or less, or 11% by weight or less. As a specific example, the polyurethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 10% to 11% by weight.
[0177] The isocyanate terminal group content (NCO%) of the polyurethane-based prepolymer can be designed by comprehensively adjusting the types and contents of the isocyanate compounds and polyol compounds used to prepare the polyurethane-based prepolymer, the process conditions such as temperature, pressure and time during the preparation of the polyurethane-based prepolymer, and the types and contents of the additives used to prepare the polyurethane-based prepolymer.
[0178] If the isocyanate terminal group content (NCO%) of the polyurethane-based prepolymer meets the above range, the reaction rate, reaction time and final cured structure in the subsequent reaction between the polyurethane-based prepolymer and the curing agent can be adjusted based on the use and purpose of the final polishing pad to facilitate polishing performance.
[0179] In one embodiment, the polyurethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 8% to 10% by weight, for example, 8% to 9.4% by weight. If the NCO% of the polyurethane-based prepolymer is less than the above range, the electrical properties based on the chemical hardening structure in the polishing pad may not achieve the desired polishing performance in terms of polishing rate and flatness, and there may be a problem of reducing the life of the polishing pad due to excessive increase in pad cutting rate or cutting wear rate. On the other hand, if the NCO% exceeds the above range, surface defects such as scratches and chatter marks on the semiconductor substrate may increase.
[0180] Foaming agent
[0181] The foaming agent is a component used to form a pore structure in the polishing layer, and may include one selected from a solid-phase foaming agent, a gas-phase foaming agent, a liquid-phase foaming agent, and a combination thereof.
[0182] According to one embodiment, the foaming agent may be a non-chlorine-based foaming agent that does not contain a chlorine component. Specifically, it may not contain or minimize the use of chlorine-based foaming agent components that are commonly used to prepare polishing pads, such as vinylidene chloride (VDC). For example, based on the total weight of the foaming agent, the content of the non-chlorine-based foaming agent may be 50% or more by weight, 80% or more by weight, 90% or more by weight, 95% or more by weight, 97% or more by weight, 99% or more by weight, or 99.5% or more by weight, and is 100% or less by weight or 99.5% or less by weight, as a specific example, 80% to 100% by weight, 90% to 100% by weight, or 80% to 99.5% by weight. In addition, the content of the chlorine-based blowing agent may be 20% by weight or less, 10% by weight or less, 5% by weight or less, 1% by weight or less, 0.5% by weight or less, or 0.3% by weight or less, based on the total weight of the blowing agent, and is 0% by weight or more, 0.1% by weight or more, 0.5% by weight or more, as specific examples, 0% by weight to 20% by weight, 0% by weight to 1% by weight, 0% by weight to 0.5% by weight, or 0.5% by weight to 20% by weight.
[0183] The foaming agent may be at least one selected from a solid-phase foaming agent including particles having a hollow structure, a liquid-phase foaming agent using a volatile liquid, and an inert gas.
[0184] As an example, a solid phase foaming agent may include particles having a hollow structure that have been expanded and sized by heat. Such a solid phase foaming agent has the advantage of controlling the pore size uniformly because it is used in the raw material in an already foamed form and has a uniform particle size.
[0185] In addition, the solid phase foaming agent may contain expandable particles. Expandable particles are particles having the property of being expandable by heat or pressure. Their size in the final polishing layer can be determined by the heat or pressure applied during the preparation of the polishing layer. The expandable particles are used in the raw material in a particle state that has not yet expanded. Their final size is determined when they expand by applying heat or pressure during the preparation of the polishing layer.
[0186] The average particle size of the solid-phase foaming agent may be 5 μm to 100 μm, specifically, 5 μm to 50 μm or 20 μm to 50 μm. When the solid-phase foaming agent is a particle used in a raw material in an expanded state as described below, the average particle size of the solid-phase foaming agent may refer to the average particle size of the expanded particles themselves. When the solid-phase foaming agent is a particle used in a raw material in an unexpanded state as described below, it may refer to the average particle size after the particles are expanded by heat or pressure during the preparation process.
[0187] The solid phase foaming agent in the form of expandable particles may include a resin shell and an expansion inducing component encapsulated in the shell. These expandable particles may be formed into a hollow structure by heating during the preparation process to evaporate the encapsulated expansion inducing component.
[0188] For example, the housing may include a thermoplastic resin. The thermoplastic resin may be at least one selected from the group consisting of acrylonitrile-based copolymers, methacrylonitrile-based copolymers, and acrylic copolymers.
[0189] The thickness of the shell may be, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, or 3 μm or more, and 15 μm or less, 12 μm or less, or 10 μm or less, and as a specific example, may be 2 μm to 15 μm.
[0190] The expansion inducing component may include one selected from hydrocarbon compounds, tetraalkylsilane compounds and combinations thereof. Specifically, the hydrocarbon may include one selected from ethane, ethylene, propane, propylene, n-butane, isobutane, n-butene, isobutylene, n-pentane, isopentane, neopentane, n-hexane, heptane, petroleum ether and combinations thereof. The tetraalkylsilane compound may include a compound selected from tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, trimethyl-n-propylsilane and combinations thereof.
[0191] The solid-phase foaming agent may include particles treated with an inorganic component. In one embodiment, the solid-phase foaming agent may be a foaming agent treated with silicon dioxide (SiO2) particles. Treating the solid-phase foaming agent with an inorganic component can prevent aggregation between multiple particles. In terms of the chemical, electrical and / or physical properties of the foaming agent surface, the solid-phase foaming agent treated with an inorganic component may be different from a solid-phase foaming agent not treated with an inorganic component.
[0192] Commercial products of solid phase foaming agents include 920DE20d70, 051DET40d25 and 051DET40d42 from Nouryon and F-65DE, F-80DE and FN-80SDE from Matsumoto.
[0193] As a specific example, the foaming agent used in the polishing pad according to the embodiment includes a solid-phase foaming agent. The solid-phase foaming agent may include at least one selected from the group consisting of acrylonitrile-based copolymers, methyl methacrylate-based copolymers, methacrylonitrile-based copolymers, and acrylic acid-based copolymers.
[0194] The content of the solid-phase foaming agent may be 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more, and 5 parts by weight or less, 3 parts by weight or less, or 2 parts by weight or less, relative to 100 parts by weight of the polyurethane-based prepolymer. As a specific example, the content of the solid-phase foaming agent may be 0.1 parts by weight to 5 parts by weight or 0.5 parts by weight to 2 parts by weight relative to 100 parts by weight of the polyurethane-based prepolymer.
[0195] The type and content of the solid phase foaming agent can be designed according to the pore structure and physical properties required for the polishing layer.
[0196] At the same time, during the mixing reaction of the prepolymer and the curing agent, a liquid-phase foaming agent can be introduced to form pores. It does not participate in the reaction between the prepolymer and the curing agent. In addition, the liquid-phase foaming agent is physically evaporated by the heat generated during the mixing and reaction of the prepolymer and the curing agent, thereby forming pores.
[0197] The volatile liquid-phase blowing agent can be liquid at 25°C, and it does not react with isocyanate groups, amide groups and alcohol groups. Specifically, the volatile liquid-phase blowing agent can be selected from cyclopentane, n-pentane, cyclohexane, n-butyl acetate, bis(nonafluorobutyl)(trifluoromethyl)amine, and perfluorotributylamine, perfluoro-N-methylmorpholine, perfluorotripentylamine and perfluorohexane and other perfluoro compounds. Commercially available perfluoro compound products include FC-40 (3M), FC-43 (3M), FC-70 (3M), FC-72 (3M), FC-770 (3M), FC-3283 (3M) and FC-3284 (3M).
[0198] In addition, the foaming agent may include a gas phase foaming agent. For example, the foaming agent may include a solid phase foaming agent and a gas phase foaming agent.
[0199] The gas phase foaming agent may include an inert gas. When the polyurethane-based prepolymer and the curing agent react, the gas phase foaming agent is added as a component for forming pores.
[0200] The type of inert gas is not particularly limited, as long as it is a gas that does not participate in the reaction of the polyurethane-based prepolymer and the curing agent. For example, the inert gas may include one selected from nitrogen (N2), carbon dioxide (CO2), argon (Ar), helium (He) and a combination thereof.
[0201] The type and content of the gas phase foaming agent can be designed according to the desired pore structure and physical properties of the polishing layer.
[0202] Inert gas can be fed with a volume of 10% to 30% based on the total volume of the composition. Specifically, inert gas can be fed with a volume of 15% to 30% based on the total volume of the composition. Specifically, the gas-phase foaming agent can be fed by a predetermined feed pipe, while the polyurethane-based prepolymer, solid-phase foaming agent and curing agent are mixed. The feed rate of the gas-phase foaming agent is from about 0.8L / minute to about 2.0L / minute, for example, from about 0.8L / minute to about 1.8L / minute, for example, from about 0.8L / minute to about 1.7L / minute, for example, from about 1.0L / minute to about 2.0L / minute, for example, from about 1.0L / minute to about 1.8L / minute, for example, from about 1.0L / minute to about 1.7L / minute.
[0203] Curing agent
[0204] The curing agent is a compound for chemically reacting with the polyurethane-based prepolymer to form a final cured structure in the polishing layer. For example, it may include an amine compound or an alcohol compound. Specifically, the curing agent may include one selected from aromatic amines, aliphatic amines, aromatic alcohols, aliphatic alcohols, and combinations thereof.
[0205] According to an embodiment, the curing agent may include a non-chlorine-based curing agent that does not contain a chlorine component. For example, the content of the non-chlorine-based curing agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more based on the total weight of the curing agent, and may be 100% by weight or less or 99.5% by weight or less, and as a specific example, may be 80% by weight to 100% by weight, 90% by weight to 10% by weight, or 80% by weight to 99.5% by weight. In addition, the content of the chlorine-based curing agent may be 20% by weight or more, 10% by weight or more, 5% by weight or more, 1% by weight or more, 0.5% by weight or more, or 0.3% by weight or more, and 0% by weight or less, 0.1% by weight or less, or 0.5% by weight or less, based on the total weight of the curing agent, and as a specific example, may be 0% to 20% by weight, 0% to 1% by weight, 0% to 0.5% by weight, or 0.5% to 20% by weight.
[0206] The curing agent may be at least one selected from a solid-phase curing agent and a liquid-phase curing agent.
[0207] The solid phase curing agent may contain an active hydrogen group. The solid phase curing agent may contain an amine group (-NH2) as an active hydrogen group.
[0208] In addition, the solid phase curing agent may be an ester compound containing two or more benzene rings. Specifically, the solid phase curing agent may contain two or more ester groups in the molecule.
[0209] The solid phase curing agent may have a weight average molecular weight of 150 to 400, such as 150 to 350, such as 200 to 350, such as 250 to 350, such as 300 to 350. The solid phase curing agent may have a melting point (mp) of 100°C to 150°C, such as 100°C to 140°C, such as 110°C to 130°C.
[0210] In one embodiment, the solid phase curing agent includes at least one selected from 1,3-propylene glycol bis(4-aminobenzoate) (PDPAB), 4-(4-aminobenzoyl)4-aminobenzoyloxyphenyl ester, 4-(4-aminobenzoyl)4-aminobenzoyloxybutyl ester, 4-[4-(4-aminobenzoyl)oxy-3-methylbutyloxy]4-aminobenzoic acid butyl ester and methylene bis-methyl anthranilate (MBNA).
[0211] The liquid phase curing agent may contain an active hydrogen group. The liquid phase curing agent may contain at least one selected from an amine group (-NH2), a hydroxyl group (-OH), a carboxylic acid group (-COOH), an epoxy group and a combination thereof as an active hydrogen group. Specifically, it may contain an amine group (-NH2).
[0212] In addition, the liquid phase curing agent may contain sulfur in the molecule. Specifically, it may contain two or more sulfur elements in the molecule.
[0213] The liquid curing agent may have a weight average molecular weight of 50 to 300, such as 100 to 250, such as 150 to 250, such as 200 to 250.
[0214] In addition, the liquid phase curing agent may be in a liquid state at room temperature. Alternatively, the boiling point (bp) of the liquid phase curing agent may be 160°C to 240°C, specifically 170°C to 240°C, and more specifically 170°C to 220°C.
[0215] Examples of the liquid-phase curing agent include at least one selected from 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, and N,N′-bis(sec-butylamino)diphenylmethane.
[0216] In addition, the curing agent may further include other curing agents in addition to the liquid phase curing agent and the solid phase curing agent. The additional curing agent may be, for example, at least one of an amine compound and an alcohol compound. Specifically, the additional curing agent may include at least one compound selected from aromatic amines, aliphatic amines, aromatic alcohols and aliphatic alcohols.
[0217] For example, the additional curing agent can be at least one selected from diaminodiphenylmethane, diaminodiphenyl sulfone, meta-xylylenediamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, ethylene glycol, diethylene glycol, dipropylene glycol, butanediol, hexylene glycol, glycerol and trimethylolpropane.
[0218] As a specific example, the curing agent may include at least one selected from diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propylene glycol bis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutyl]butyl 4-aminobenzoate, and dimethylaminobenzoic acid methylene (MBNA).
[0219] The content of the curing agent may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, and may be 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less, relative to 100 parts by weight of the polyurethane-based prepolymer. The content of the curing agent may be 10 to 40 parts by weight, more specifically, 15 to 35 parts by weight or 15 to 25 parts by weight, relative to 100 parts by weight of the polyurethane-based prepolymer.
[0220] additive
[0221] The composition for preparing the polishing layer may further include other additives such as surfactants and reaction rate controllers. Names such as "surfactant" and "reaction rate controller" are self-defined names based on the main effects of the substances. The corresponding substances do not necessarily perform functions limited to the effects defined by the names.
[0222] The surfactant is not particularly limited as long as it plays a role in preventing pores from agglomerating and overlapping with each other. For example, the surfactant may include a silicon-based surfactant.
[0223] Relative to 100 parts by weight of the polyurethane-based prepolymer, the amount of the surfactant can be 0.2 to 2 parts by weight. Specifically, relative to 100 parts by weight of the polyurethane-based prepolymer, the surfactant can be used in an amount of 0.2 to 1.9 parts by weight, such as 0.2 to 1.8 parts by weight, such as 0.2 to 1.7 parts by weight, such as 0.2 to 1.6 parts by weight, such as 0.2 to 1.5 parts by weight, such as 0.5 to 1.5 parts by weight. If the amount of the surfactant is within the above range, the pores produced by the gas-phase foaming agent can be stably formed and maintained in the mold.
[0224] The reaction rate controller plays a role in promoting or delaying the reaction. Depending on the purpose, a reaction promoter, a reaction delay agent or both can be used. The reaction rate controller may include a reaction promoter. For example, the reaction rate controller may be at least one reaction promoter selected from a tertiary amine compound and an organometallic compound.
[0225] Specifically, the reaction rate controller may include at least one of triethyldiamine, dimethylethylethylamine, tetramethylbutylene diamine, 2-methyl-triethyldiamine, dimethylethyldiethylamine, triisopropylamine, 1,4-diazobicyclo (2,2,2) octane, di(2-methylaminoethyl) ether, trimethylaminoethylethanolamine, N,N,N,N,N''-pentamethyldiethyltriamine, dimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, N-dimethylaminoethylmorpholine, N-dimethylcyclohexylamine, 2-methyl-2-azine keel, dibutyltin dilaurate, octadecanoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin maleate, di-2-ethylhexanoate dibutyltin and dibutyltin dithiol. Specifically, the reaction rate controller may include at least one selected from benzyldimethylamine, N,N-dimethylcyclohexylamine and triethylamine.
[0226] Relative to 100 parts by weight of the polyurethane-based prepolymer, the amount of the reaction rate controller can be 0.05 to 2 parts by weight. Specifically, relative to 100 parts by weight of the polyurethane-based prepolymer, the reaction rate controller can be used in an amount of 0.05 to 1.8 parts by weight, such as 0.05 to 1.7 parts by weight, such as 0.05 to 1.6 parts by weight, such as 0.1 to 1.5 parts by weight, such as 0.1 to 0.3 parts by weight, such as 0.2 to 1.8 parts by weight, such as 0.2 to 1.7 parts by weight, such as 0.2 to 1.6 parts by weight, such as 0.2 to 1.5 parts by weight, such as 0.5 to 1 parts by weight. If the reaction rate controller is used within the above content range, the curing reaction rate of the prepolymer composition can be appropriately controlled to form a polishing layer with pores of desired size and hardness.
[0227] Support layer
[0228] The support layer constitutes a subpad for supporting the polishing layer and absorbing and dispersing the impact applied to the polishing layer. Therefore, during the polishing process using the polishing pad, it minimizes damage and defects of the object to be polished.
[0229] The support layer may include nonwoven fabric or suede, but is not limited thereto.
[0230] In one embodiment, the support layer may be a resin-impregnated nonwoven fabric. The nonwoven fabric may be a fiber nonwoven fabric including one selected from polyester fiber, polyamide fiber, polypropylene fiber, polyethylene fiber and a combination thereof.
[0231] The resin impregnated in the non-woven fabric may include polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester-based elastomer resin, polyamide-based elastomer resin and combinations thereof.
[0232] The thickness of the support layer may be, for example, 0.3 mm or more or 0.5 mm or more, and 3 mm or less, 2 mm or less, or 1 mm or less. As a specific example, the thickness of the support layer may be 0.3 mm to 3 mm or 0.5 mm to 1 mm.
[0233] The hardness of the support layer may be, for example, 50 Asker C or more, 60 Asker C or more, or 70 Asker C or more, and 100 Asker C or less, 90 Asker C or less, or 80 Asker C or less. As a specific example, the hardness of the support layer may be 50 Asker C to 100 Asker C or 60 Asker C to 90 Asker C.
[0234] Additionally, an adhesive layer may be interposed between the polishing layer (top pad) and the support layer (sub pad).
[0235] The adhesive layer may include a hot melt adhesive. The hot melt adhesive may be at least one selected from polyurethane resin, polyester resin, ethylene-vinyl acetate resin, polyamide resin and polyolefin resin. Specifically, the hot melt adhesive may be at least one selected from polyurethane resin and polyester resin.
[0236] In addition, the double-sided tape can be laminated under the support layer. When applied to the CMP equipment, after removing the release paper of the double-sided tape, it is attached to the platen for use.
[0237] Preparation method of polishing pad
[0238] The method for preparing a polishing pad according to an embodiment includes preparing a composition for a polishing pad, the composition including a polyurethane-based prepolymer, a foaming agent and a curing agent; injecting the composition for a polishing pad into a mold and curing to prepare a polishing layer; and laminating the polishing layer with a support layer.
[0239] The specific types and contents of the polyurethane-based prepolymer, curing agent and foaming agent are as described above.
[0240] As a specific example, the foaming agent includes a solid-phase foaming agent, the solid-phase foaming agent includes at least one of an acrylonitrile-based copolymer, a methyl methacrylate-based copolymer, a methacrylonitrile-based copolymer and an acrylic acid-based copolymer, and the curing agent includes at least one of diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propylene glycol bis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-phenylenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutyl]butyl 4-aminobenzoate, and methylene dimethyl benzoate (MBNA).
[0241] The composition for the polishing pad may be prepared by sequentially or simultaneously mixing a polyurethane-based prepolymer, a blowing agent, and a curing agent.
[0242] As an example, the step of preparing the composition for the polishing pad may be performed by mixing a polyurethane-based prepolymer with a curing agent and then further mixing with a foaming agent, or mixing a polyurethane-based prepolymer with a foaming agent and then further mixing with a curing agent.
[0243] As another example, the polyurethane-based prepolymer, curing agent, and blowing agent may be put into the mixing process substantially at the same time. If blowing agent, surfactant, and inert gas are further added, they may be put into the mixing process substantially at the same time.
[0244] As another example, a polyurethane-based prepolymer, a foaming agent, and a surfactant may be pre-mixed, and then a curing agent or a curing agent with an inert gas may be introduced.
[0245] The mixing initiates the reaction of the polyurethane-based prepolymer and the curing agent, so that the blowing agent and the inert gas are uniformly dispersed in the raw material. In this case, the reaction rate controller can intervene in the reaction between the polyurethane-based prepolymer and the curing agent from the beginning of the reaction, thereby controlling the reaction rate. Specifically, the mixing can be carried out at a rotation speed of 1000 to 10000 rpm or 4000 to 7000 rpm. Within the above speed range, it can be more conducive to the uniform dispersion of the inert gas and the blowing agent in the raw material.
[0246] In addition, the step of preparing the composition for a polishing pad may be performed at 50° C. to 150° C. If necessary, it may be performed under vacuum defoaming conditions.
[0247] If the foaming agent includes a solid-phase foaming agent, the step of preparing the composition for the polishing pad may include mixing a polyurethane-based prepolymer and a solid-phase foaming agent to prepare a first preliminary composition; and mixing the first preliminary composition and a curing agent to prepare a second preliminary composition.
[0248] The first preliminary composition may have a viscosity of about 1000 cps to about 2000 cps, for example about 1000 cps to about 1800 cps, for example about 1000 cps to about 1600 cps, for example about 1000 cps to about 1500 cps at about 80°C.
[0249] If the foaming agent includes a gas-phase foaming agent, the step of preparing the composition for the polishing pad may include preparing a third preliminary composition including a polyurethane-based prepolymer and a curing agent; adding the gas-phase foaming agent to the third preliminary composition to prepare a fourth preliminary composition. In one embodiment, the third preliminary composition may further include a solid-phase foaming agent.
[0250] In one embodiment, the step of preparing the polishing layer includes preparing a mold preheated to a first temperature; injecting the polishing pad composition into the preheated mold and curing it; and post-curing the curing composition for the polishing pad at a second temperature higher than the preheating temperature.
[0251] In one embodiment, the temperature difference between the first temperature and the second temperature may be about 10° C. to about 40° C., such as about 10° C. to about 35° C., such as about 15° C. to about 35° C. In one embodiment, the first temperature may be about 60° C. to about 100° C., such as about 65° C. to about 95° C., such as about 70° C. to about 90° C. In one embodiment, the second temperature may be about 100° C. to about 130° C., such as about 100° C. to about 125° C., such as about 100° C. to about 120° C.
[0252] The step of curing the composition for a polishing pad at the first temperature may be performed for about 5 minutes to about 60 minutes, such as about 5 minutes to about 40 minutes, such as about 5 minutes to about 30 minutes, such as about 5 minutes to about 25 minutes.
[0253] The step of post-curing the composition for a polishing pad cured at the first temperature at the second temperature can be performed for about 5 hours to about 30 hours, for example, about 5 hours to about 25 hours, for example, about 10 hours to about 30 hours, for example, about 10 hours to about 25 hours, for example, about 12 hours to about 24 hours, for example, about 15 hours to about 24 hours.
[0254] Thereafter, the step of injecting the composition for a polishing pad into the mold and curing it may be performed under a temperature condition of 60° C. to 120° C. and a pressure condition of 50 kg / m 2 to 200 kg / m 2 .
[0255] In addition, the above preparation method may further include the steps of cutting the surface of the polishing pad obtained, machining grooves on the surface, bonding it to the bottom, inspecting, packaging, etc. These steps can be carried out in a conventional manner for preparing a polishing pad.
[0256] As an example, the method of preparing a polishing pad may further include machining at least one side of the polishing layer. The step of machining at least one side of the polishing layer may include forming grooves on at least one side of the polishing layer; wire turning at least one side of the polishing layer; and roughening at least one side of the polishing layer.
[0257] The grooves may include at least one concentric circular groove spaced apart from the center of the polishing layer at a certain interval; and radial grooves continuously connected from the center of the polishing layer to the edge of the polishing layer. Wire turning may be performed by cutting the polishing layer to a certain thickness using a cutting tool. Roughening may be performed by mechanically processing the surface of the polishing layer with a sanding roller.
[0258] Method for preparing semiconductor device
[0259] Semiconductor devices can be manufactured by performing chemical and mechanical polishing using the above-mentioned polishing pad.
[0260] A method of manufacturing a semiconductor device according to an embodiment includes irradiating a polishing layer of a conditioning polishing pad with ultraviolet light having a wavelength of 100 nm to 380 nm while chemically and mechanically polishing a semiconductor substrate using the polishing pad.
[0261] Specifically, the process for preparing a semiconductor device includes relatively rotating a polishing layer of a polishing pad and a surface of a semiconductor substrate while they are in contact with each other to polish the surface of the semiconductor substrate. In addition, the method for preparing a semiconductor device includes conditioning the polishing layer of the polishing pad by irradiating ultraviolet light having a wavelength of 100 nm to 380 nm.
[0262] Figure 7 and Figure 8 FIG. 2 shows a configuration of an apparatus for irradiating ultraviolet light during a CMP process according to an embodiment. Figure 7 and Figure 8 The ultraviolet lamp (700) is installed above the polishing pad (100) of the apparatus according to the embodiment. The ultraviolet lamp can be configured to adjust the angle and height. The ultraviolet lamp can irradiate light with a wavelength range of 100nm to 380nm to the polishing pad.
[0263] Figure 2 The occurrence of defects caused by debris in the process of manufacturing semiconductor devices is shown. Figure 2 , the debris (150) generated by the polishing layer may cause defects (650) or scratches on the surface of the semiconductor device. However, the polishing pad according to the embodiment has the characteristic that the particle size of the debris is reduced when ultraviolet light is irradiated during the CMP process. Therefore, by utilizing these characteristics of the polishing pad, irradiating ultraviolet light during the CMP process can minimize the occurrence of defects and scratches in the semiconductor device. Therefore, when a semiconductor device is prepared by a CMP process using the polishing pad according to the embodiment, CMP performance and yield can be improved.
[0264] Hereinafter, a method of manufacturing a semiconductor device according to an embodiment will be described in detail.
[0265] First, once the polishing pad (100) according to the embodiment has been attached to the platen (200), the semiconductor substrate (600) to be polished is placed on the polishing pad (100). In this case, the surface of the semiconductor substrate (600) to be polished is in direct contact with the polishing surface of the polishing pad (100). For polishing, CMP slurry (450) can be supplied to the polishing pad through the slurry supplier (400). The flow rate of the CMP slurry (450) supplied by the slurry supplier (400) can be about 10 cm / s depending on the purpose. 3 / min to about 1000cm 3 / minute. For example, it can be about 50cm 3 / min to about 500cm 3 / minute, but not limited to this.
[0266] Thereafter, the semiconductor substrate (600) and the polishing pad (100) are rotated relative to each other, thereby polishing the surface of the semiconductor substrate (600). In this case, the rotation direction of the semiconductor substrate (600) and the rotation direction of the polishing pad (100) may be the same direction or opposite directions. The rotation speeds of the semiconductor substrate (600) and the polishing pad (100) may be selected in the range of about 10 rpm to about 500 rpm, respectively, according to the purpose. For example, it may be about 30 rpm to about 200 rpm, but is not limited thereto.
[0267] The semiconductor substrate (600) mounted on the polishing head (510) is pressed against the polishing surface of the polishing pad (100) with a predetermined load to contact the polishing pad, and then the surface thereof can be polished. The load applied by the polishing head (510) to the polishing surface of the polishing pad (100) and the surface of the semiconductor substrate (600) can be between about 1 gf / cm2 and about 1 gf / cm3 according to the purpose. 2 To about 1000gf / cm 2 For example, it can be about 10 gf / cm 2 To about 800gf / cm 2 , but not limited to this.
[0268] In one embodiment, the semiconductor substrate (600) as the object to be polished may include an oxide layer, a tungsten layer or a composite layer thereof. Specifically, the semiconductor substrate (600) may include an oxide layer, a tungsten layer or a composite layer of an oxide layer and a tungsten layer. The composite layer of the oxide layer and the tungsten layer may be a multilayer film in which a tungsten layer is stacked on one side of the oxide layer, or may be a single layer film in which an oxide region and a tungsten region are mixed in a single layer. Since the object to be polished has such a film material and the polishing pad has the characteristics according to the embodiment at the same time, the semiconductor device manufactured according to the method for manufacturing a semiconductor device may have minimal defects.
[0269] In one embodiment, the method for preparing a semiconductor device may further include: in the step of polishing the object to be polished, providing any one of a slurry for polishing an oxide layer and a slurry for polishing a tungsten layer. Alternatively, the slurry for polishing the oxide layer and the slurry for polishing the tungsten layer are sequentially supplied to the polishing surface.
[0270] For example, if the semiconductor substrate as the object to be polished includes an oxide layer, the method for preparing a semiconductor device may include supplying a slurry for polishing the oxide layer. If the semiconductor substrate includes a tungsten layer, the method for preparing a semiconductor device may include supplying a slurry for polishing the tungsten layer. If the semiconductor substrate includes a composite layer of an oxide layer and a tungsten layer, the method for preparing a semiconductor device may include sequentially supplying a slurry for polishing the oxide layer and a slurry for polishing the tungsten layer to the polishing surface. Here, depending on the process, the slurry for polishing the oxide layer may be supplied first, and then the slurry for polishing the tungsten layer may be supplied, or the slurry for polishing the tungsten layer may be supplied first, and then the slurry for polishing the oxide layer may be supplied.
[0271] In one embodiment, in order to maintain the polishing surface of the polishing pad (100) in a state suitable for polishing, the method for preparing a semiconductor device may further include treating the polishing surface of the polishing pad (100) with a dresser (300) while polishing the semiconductor substrate (600).
[0272] In addition, the process for preparing a semiconductor device includes conditioning a polishing layer of a polishing pad while irradiating with ultraviolet light having a wavelength of 100 nm to 380 nm. In the device according to the embodiment, an ultraviolet lamp (700) is installed above the polishing pad (100). The ultraviolet lamp can be configured to adjust the angle and height.
[0273] For example, the height of the ultraviolet lamp from the surface of the polishing pad (100) may be 2 cm to 30 cm, specifically, 3 cm to 10 cm, more specifically, 3 cm to 7 cm.
[0274] In addition, the ultraviolet light intensity of the surface of the polishing pad (100) may be 100w to 2kW, more specifically, 500w to 1.5kW.
[0275] In addition, the irradiation time of the ultraviolet light can be more than 1 minute, more than 2 minutes, or more than 3 minutes, and less than 20 minutes, less than 10 minutes, less than 7 minutes, less than 5 minutes, or less than 4 minutes. For example, the irradiation time of the ultraviolet light can be 1 minute to 20 minutes, 1 minute to 10 minutes, 2 minutes to 10 minutes, 1 minute to 7 minutes, 1 minute to 5 minutes, or 2 minutes to 5 minutes. As a specific example, the irradiation time of the ultraviolet light can be 2 minutes to 4 minutes.
[0276] Mode for Carrying Out the Invention
[0277] Although the following examples are described, the scope of possible implementations is not limited thereto.
[0278] Polishing Pad Preparation and Evaluation
[0279] Examples A1 to A7 and Comparative Examples A1 and A2: Preparation of Polishing Pads
[0280] Step (1) Preparation of prepolymer
[0281] Toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG) were added to a four-necked flask and then reacted at 80° C. for 3 hours, thereby preparing a polyurethane-based prepolymer. The NCO% of the prepolymer was measured and shown in Table 1 below.
[0282] Step (2) Preparation of polishing pad
[0283] A casting machine is provided, which is equipped with a tank and a feed line for raw materials such as prepolymers, curing agents, inert gases and blowing agents. The polyurethane-based prepolymer, blowing agent, curing agent, inert gas (N2) and silicon-based surfactant (Evonik) prepared above are respectively loaded into the tank. The raw materials are stirred and fed to the mixing head at a constant rate through their respective feed lines. The blowing agent and curing agent shown in Table 1 are used. The prepolymer and curing agent are fed in an equivalent ratio of 1:1, and the total feed rate is 10kg / min.
[0284] A mold (1000 mm × 1000 mm × 3 mm) was prepared and preheated at 80° C. The mixed raw materials prepared above were injected into the mold and reacted to obtain a solid cake-shaped molded product. Thereafter, the top and bottom of the molded product were ground to obtain a polishing layer for the top pad.
[0285] Thereafter, the polishing layer is subjected to surface milling and grooving steps and is laminated with the support layer of the subpad by hot melt adhesive, thereby preparing a polishing pad.
[0286] Double-sided tape (442JS, 3M) was laminated under the support layer so that it could be attached to the platen of the CMP equipment.
[0287] The curing agent and foaming agent used in the Examples and Comparative Examples are shown below.
[0288] DMTDA: 3,5-dimethylthio-2,6-diaminotoluene, Covestro
[0289] MOCA: 4,4'-methylenebis(2-chloroaniline), Ishihara
[0290] F-65DE: Acrylonitrile / methyl methacrylate / methacrylonitrile copolymer, expanded pore type, Matsumoto
[0291] F-80DE: Acrylonitrile / methyl methacrylate / methacrylonitrile copolymer, expanded pore type, Matsumoto
[0292] 051DET40d25: Acrylonitrile / Methacrylonitrile Copolymer, Expanded Cell Type, Nouryon
[0293] 051DET40d42: Acrylonitrile / Methacrylonitrile Copolymer, Expanded Cell Type, Nouryon
[0294] 461DET40d25: Acrylonitrile / ethylene dichloride, expanded pore type, Nouryon
[0295] Details of the examples and comparative examples are summarized in Table 1 below.
[0296] [Table 1]
[0297]
[0298] Seq.: Sequential test example A1
[0299] The polishing layer, support layer and polishing pad laminated therefrom prepared as described above were respectively subjected to the following tests.
[0300] (1) Hardness
[0301] Each sample was cut into 5 cm×5 cm (thickness: 2 mm) and stored at room temperature and temperatures of 30° C., 50° C., and 70° C. for 12 hours, respectively, to measure Shore D hardness and Asker C hardness using a durometer.
[0302] (2) Density
[0303] Each sample was cut into 2 cm×5 cm (thickness: 2 mm) and stored at a temperature of 25° C. for 12 hours to measure the density using a gravimeter.
[0304] (3) Tensile strength
[0305] Each sample was cut into 4 cm×1 cm (thickness: 2 mm). The samples were tested using a universal testing machine (UTM) at a rate of 50 mm / min, while measuring the ultimate strength before fracture.
[0306] (4) Elongation
[0307] Each sample was cut into 4 cm × 1 cm (thickness: 2 mm). The sample was tested using a universal testing machine (UTM) at a rate of 50 mm / min to measure the maximum deformation before fracture. The ratio of the maximum deformation to the initial length was expressed as a percentage (%).
[0308] The results are shown in the following table.
[0309] [Table 2]
[0310]
[0311] NW cloth: non-woven fabric
[0312] As shown in the above table, the polishing pads of Examples A1 to A7 are at least equal to the polishing pads of Comparative Examples A1 and A2 in hardness, density, tensile strength, and elongation.
[0313] Test Example A2
[0314] The polishing pads prepared above were subjected to the following tests.
[0315] (1) Polishing speed (removal rate)
[0316] On a CMP polisher, a silicon wafer with a diameter of 300 mm on which silicon oxide was deposited by a CVD process was placed on a porous polyurethane polishing pad mounted on a platen, with the silicon oxide layer of the silicon wafer facing downward.
[0317] Then, the silicon oxide layer was polished under a polishing load of 4.0 psi while the polishing pad was rotated at 150 rpm, calcined cerium dioxide slurry was supplied onto the polishing pad at a rate of 250 ml / min, and a platen was placed on the polishing pad, which was rotated at 150 rpm for 60 seconds.
[0318] After polishing, the silicon wafer was separated from the carrier, mounted in a spin dryer, rinsed with deionized water (DIW), and then dried with nitrogen for 15 seconds. The film thickness of the dried silicon wafer before and after polishing was measured using a spectroscopic reflectometer type thickness measuring instrument (manufacturer: Keyence, model: SI-F80R).
[0319] Thereafter, the polishing speed is calculated using the following Mathematical Formula 1.
[0320] [Mathematical formula 1]
[0321]
[0322] (2) Defects
[0323] Polishing was performed using a CMP polisher in the same manner as the polishing speed test. After polishing, the silicon wafer was transferred to a cleaner and cleaned for 10 seconds each using 1% HF, 1% H2NO3, and deionized water (DIW). Thereafter, it was transferred to a spin dryer, washed with deionized water (DIW), and then dried with nitrogen for 15 seconds. The defect change of the dried silicon wafer before and after polishing was measured using a defect measurement device (manufacturer: Tenkor, model: XP+). Specifically, the total number of scratches, vibration marks, pits, and residues on the wafer surface was measured.
[0324] (3) Chlorine content
[0325] A circular sample with a size of 3 cm in diameter and 0.3 cm in height is prepared from the polishing layer of the polishing pad. The chlorine content in the sample can be measured by IEC 62321-3-2, which is an international standard for measuring specific substances in polymers by combustion ion chromatography (C-IC).
[0326] (4) Crumb size (D50 size)
[0327] a) Obtaining an aqueous solution of the crumbs
[0328] A porous polyurethane polishing pad was attached to the platen of a CMP polishing machine. Thereafter, the operation of the carrier was excluded, and only the trimmer and deionized water (DIW) were used to collect the debris of the polishing layer. CI45 (pad cutting rate of 80 to 90 μ0 cutting rate, Saesol) was used as the material, and the polishing layer was trimmed under the conditions of a platen speed of 93 rpm, a trimmer load of 9 lbs, a rotation speed of 64 rpm, and a scanning speed of 19 times / minute, while deionized water was supplied at 300 cc / min. The polishing layer debris formed after 10 minutes of trimming was collected in the form of a deionized water mixed solution, thereby obtaining 300 mL of a debris aqueous solution.
[0329] b) pH adjustment and crumb size analysis
[0330] The pH of the chip solution was 6.0 to 6.5, and the pH was adjusted to 5.5 using nitric acid solution. Here, the concentration of the nitric acid solution used was 35%. The D50 particle size of the chip in the chip solution was measured using a particle size analyzer (Mastersize 3000, Malvern) and a medium capacity automatic disperser (Hydro MV, Malvern). The analyzer was set to a polyurethane with a refractive index of 1.55 for the material to be analyzed, a deionized water with a refractive index of 1.33 for the dispersant, and a stirring speed of 2500 rpm.
[0331] (5) Potential difference
[0332] An aqueous solution of the chips is obtained in the same manner as in section (4) (a) above.
[0333] In order to ensure the particle stability in the debris aqueous solution, it was kept at room temperature for 24 hours to precipitate particles with a particle size of more than 20 μm. Then the supernatant within 10 mm from the top surface of the solution was taken as a sample. The pH value of the obtained sample was 6.0 to 6.5. The pH was adjusted to 5.5 using an aqueous nitric acid solution. Here, the concentration of the aqueous nitric acid solution used was 35%. In addition, it was found that the debris concentration in the liquid sample was about 0.01% by weight. After about 5 g of the liquid sample was placed in an aluminum pan, the concentration was measured using a heated moisture meter (MX-50, AND). The potential difference of the sample was measured using a potential difference analyzer (Nano-ZS90, Malvern). Specifically, 1 mL of the sample was added to the cuvette of the potential difference analyzer and measured three times to obtain the potential difference. In this case, the device setting value was set to RI1.550 and absorbance 0.010 according to the polyurethane value.
[0334] The test results are summarized in the following table.
[0335] [Table 3]
[0336]
[0337] As can be seen from the above table, the polishing pads of Examples A1 to A7 were measured to have chlorine (Cl) contents within the desired range, and their performance, such as polishing speed, was equal to or higher than that of the polishing pads of Comparative Examples A1 and A2. Specifically, the polishing pads of Examples A1 to A7 were measured to have a smaller chip size than the polishing pads of Comparative Examples A1 and A2, and the number of defects and scratches measured was significantly less. In addition, the results of the potential difference of the polishing pads of Comparative Examples A1 to A7 were measured to be within the desired range.
[0338] (6) Relationship between debris particle size and battery difference and pH change
[0339] For the polishing pads of Examples and Comparative Examples, the chip particle size at pH 5.5 (D50[5.5]) and the chip particle size at pH 10 (D50
[10] ) were measured in the same manner as in the above section (4).
[0340] In addition, for the polishing pads of Examples and Comparative Examples, the potential difference of a chip aqueous solution with a pH of 5.5 (Zp[5.5]) and the potential difference of a chip aqueous solution with a pH of 10 (Zp
[10] ) were measured in the same manner as in the above section (5).
[0341] Here, the pH of the chip aqueous solution was adjusted by adding a nitric acid aqueous solution or a potassium hydroxide aqueous solution. Specifically, when the chip aqueous solution (pH 6.0 to 6.5) initially obtained was adjusted to pH 5.5, a nitric acid aqueous solution was added, and when it was adjusted to pH 10, a potassium hydroxide aqueous solution was added. Here, the concentration of the nitric acid aqueous solution used was 35%, and the concentration of the potassium hydroxide aqueous solution was 10%.
[0342] The following mathematical formulas (1) to (3) are calculated using the above-measured chip particle size and potential difference.
[0343] D50[5.5] / Zp[5.5]...(1)
[0344] (D50[5.5] / D50
[10] )×100...(2)
[0345] Zp[5.5]–Zp
[10] ...(3)
[0346] Wherein, D50[5.5] is the chip particle size D50 (μm) obtained when the polishing layer is repaired at a pH of 5.5, and D50
[10] is the chip particle size D50 (μm) obtained when the polishing layer is repaired at a pH of 10.
[0347] Zp[5.5] is the potential difference (mV) of an aqueous solution containing 0.01% by weight of debris obtained during conditioning of the polishing layer at a pH of 5.5, and Zp
[10] is the potential difference (mV) of an aqueous solution containing 0.01% by weight of debris obtained during conditioning of the polishing layer at a pH of 10.
[0348] The results are shown in the following table.
[0349] In addition, the test results of defects and scratches are also shown in the following table.
[0350] [Table 4]
[0351]
[0352] As can be seen from the above table, for the polishing pads of Examples A1 to A7, at a pH of 5.5, the D50 particle size of the debris obtained from the polishing layer was 50 μm or less, and at a pH of 5.5, the potential difference of the aqueous solution of the debris was measured to be in the range of -20 mV to 30 mV. In addition, for the polishing pads of Examples A1 to A7, the measured values under different pH conditions and the values of mathematical formulas (1) to (3) were all within the expected range. As a result, the number of defects and scratches generated on the silicon wafer during the CMP process was less than 20.
[0353] Specifically, for the polishing pads of Examples A1 to A3, at pH 5.5, the D50 particle size of the debris obtained from the polishing layer was 20 μm or less, and at pH 5.5, the potential difference of the aqueous solution of the debris was measured to be in the range of 0 mV to 20 mV. In addition, for the polishing pads of Examples A1 to A3, the measured values under different pH conditions and the values of mathematical formulas (1) to (3) were all within the desired range. As a result, the number of defects and scratches generated on the silicon wafer during the CMP process was very small, less than 10.
[0354] In contrast, for the polishing pads of Comparative Examples A1 and A2, the potential difference of the aqueous solution of debris obtained from the polishing layer was less than -20 mV at a pH of 5.5. Other measured values and the values of mathematical formulas (1) to (3) were also confirmed to be outside the ideal range. As a result, the number of defects and scratches generated on the silicon wafer during the CMP process increased significantly to more than 25.
[0355] Preparation of polishing pads and their evaluation under UV light irradiation
[0356] Example B1: Preparation of polishing pad
[0357] Step (1) Preparation of polyurethane-based prepolymer
[0358] 2,4-Toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethyl ether glycol (PTMEG) and diethylene glycol (DEG) were added to a four-necked flask, and then reacted at 80° C. for 3 hours to prepare a polyurethane-based prepolymer having a terminal NCO group (NCO%) content of 10% by weight.
[0359] Step (2) Preparation of polishing layer
[0360] A casting machine is provided, which is equipped with tanks and feed lines for raw materials such as prepolymers, curing agents, inert gases and foaming agents. The polyurethane-based prepolymer prepared above, curing agent (DMTDA), solid-phase foaming agent (F-65DE, Matsumoto), inert gas (N2) and silicon-based surfactant (Evonik) are respectively charged into tanks. Specifically, 32 parts by weight of curing agent, 1 part by weight of solid-phase foaming agent and 1 part by weight of surfactant are added to 100 parts by weight of prepolymer, and inert gas is charged at a speed of 1.5 L / min.
[0361] The raw materials are stirred while being fed to the mixing head at a constant rate through their respective feed lines. The rotation speed of the mixing head is about 5000 rpm. The mixed composition of the raw materials mixed in the mixing head is then injected into a mold having a width of 1000 mm, a length of 1000 mm, and a height of 3 mm. The mold temperature is adjusted to about 80 (± 5) ° C. The mixed composition solidifies in the mold and is then cast into a thin plate. The thin plate is post-cured at about 110 (± 5) ° C for about 18 hours to prepare a polishing layer.
[0362] Step (3) Preparation of polishing pad
[0363] One side of the polishing layer was wire turned using a cutting tool and grooved using a tip to have an average thickness of 2 mm. A polyester fiber nonwoven fabric was impregnated with a polyurethane resin to prepare a buffer layer. A heat seal adhesive was applied to one side of the buffer layer and the side of the polishing layer opposite to the polishing surface, respectively. The buffer layer and the polishing layer were laminated so that the two sides coated with the heat seal adhesive were in contact, and then a pressure roller was used at a temperature of about 140 (± 5) ° C and 2 kgf / cm 2 This was pressed under pressure to prepare a polishing pad.
[0364] Comparative Example B1: Preparation of polishing pad
[0365] Step (1) Preparation of polyurethane-based prepolymer
[0366] 2,4-Toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethyl ether glycol (PTMEG) and diethylene glycol (DEG) were added to a four-necked flask, and then reacted at 80° C. for 3 hours to prepare a polyurethane-based prepolymer having a terminal NCO group (NCO%) content of 9.1% by weight.
[0367] Step (2) Preparation of polishing layer
[0368] A casting machine is provided, which is equipped with a tank and a feed line for raw materials such as a prepolymer, a curing agent, an inert gas and a foaming agent. The polyurethane-based prepolymer prepared above, a curing agent (4,4′-methylenebis(2-chloroaniline) MOCA), a solid-phase foaming agent (ExpancelTM 551DE 40d42, Akzonobel), an inert gas (N2) and a silicon-based surfactant (Evonik) are respectively charged into the tank. Specifically, with respect to 100 parts by weight of the prepolymer, 25 parts by weight of the curing agent, 2.2 parts by weight of the solid-phase foaming agent and 1 part by weight of the surfactant are added, and the inert gas is added at a rate of 1.5 L / min.
[0369] The raw materials are stirred while being fed to the mixing head at a constant rate through their respective feed lines. The rotation speed of the mixing head is about 5000 rpm. The mixed composition of the raw materials mixed in the mixing head is then injected into a mold having a width of 1000 mm, a length of 1000 mm, and a height of 3 mm. The mold temperature is adjusted to about 80 (± 5) ° C. The mixed composition solidifies in the mold and is then cast into a thin plate. The thin plate is post-cured at about 110 (± 5) ° C for about 18 hours to prepare a polishing layer.
[0370] Step (3) Preparation of polishing pad
[0371] One side of the polishing layer was wire turned using a cutting tool and grooved using a tip to have an average thickness of 2 mm. A polyester fiber nonwoven fabric was impregnated with a polyurethane resin to prepare a buffer layer. A heat seal adhesive was applied to one side of the buffer layer and the side of the polishing layer opposite to the polishing surface, respectively. The buffer layer and the polishing layer were laminated so that the two sides coated with the heat seal adhesive were in contact, and then a pressure roller was used at a temperature of about 140 (± 5) ° C and 2 kgf / cm 2 This was pressed under pressure to prepare a polishing pad.
[0372] Test Example B1: Measurement of Physical Properties of Polishing Pads
[0373] The polishing layer, support layer and polishing pad laminated therefrom prepared as described above were respectively subjected to the following tests.
[0374] (1) Hardness
[0375] Each sample was cut into 5 cm×5 cm (thickness: 2 mm) and stored at room temperature and temperatures of 30° C., 50° C., and 70° C. for 12 hours, respectively, to measure Shore D hardness and Asker C hardness using a durometer.
[0376] (2) Density
[0377] Each sample was cut into 2 cm×5 cm (thickness: 2 mm) and stored at a temperature of 25° C. for 12 hours to measure the density using a gravimeter.
[0378] (3) Tensile strength
[0379] Each sample was cut into 4 cm×1 cm (thickness: 2 mm). The sample was tested at a rate of 50 mm / min using a universal testing machine (UTM) while measuring the ultimate strength before fracture.
[0380] (4) Elongation
[0381] Each sample was cut into 4 cm×1 cm (thickness: 2 mm). The sample was tested using a universal testing machine (UTM) at a rate of 50 mm / min to measure the maximum deformation before fracture. The ratio of the maximum deformation to the initial length was expressed as a percentage (%).
[0382] The results are shown in the following table.
[0383] [Table 5]
[0384]
[0385] As can be seen from the above table, the polishing pad of Example B1 is confirmed to have performance suitable for the CMP process.
[0386] Test Example B2: Changes in Crumb Particle Size with UV Light Exposure
[0387] (1) Renovation process
[0388] A porous polyurethane polishing pad was attached to the platen of a CMP polisher. Thereafter, the operation of the carrier was excluded, and only the trimmer and ceria slurry were used to collect the debris of the polishing layer. CI45 (pad cutting rate of 80 to 90 μm / hr, Saesol) was used as the material, and the polishing layer was trimmed while supplying ceria slurry at 250 mL / min under the conditions of a platen speed of 93 rpm, a trimmer load of 9 lbs, a rotation speed of 64 rpm, and a scanning speed of 19 times / min. The polishing layer debris formed after 10 minutes of trimming was collected in the form of a ceria slurry mixed solution, thereby obtaining 300 mL of a debris aqueous solution.
[0389] (2) Ultraviolet radiation
[0390] The obtained chip solution was irradiated with ultraviolet light (wavelength 100 to 380 nm) at an intensity of 1 kW from a distance of 5 cm for 10 minutes using an ultraviolet lamp (light source type: mercury lamp), and the chip solution was collected every 2 minutes. In this case, the pH value of the collected chip solution was about 10.
[0391] (3) Debris particle size analysis
[0392] The D50 particle size of the crumbs in the crumb solution was measured using a particle size analyzer (Mastersize 3000, Malvern) and a medium-volume automatic disperser (Hydro MV, Malvern). The analyzer was set to polyurethane with a refractive index of 1.55 for the material to be analyzed, deionized water with a refractive index of 1.33 for the dispersant, and a stirring speed of 2500 rpm.
[0393] The results are as follows Figure 5 ,6 and as shown in Tables 6 and 7 below.
[0394] [Table 6]
[0395]
[0396] [Table 7]
[0397]
[0398] From Tables 6, 7 and Figure 5 As can be seen in Figure 6, for the polishing pad of Example B1, the particle size of the debris decreases as the UV light exposure time elapses, and it is measured to be the smallest at 2 to 4 minutes. Thereafter, when the UV light exposure time is further extended to 6 to 8 minutes, it shows a slightly increasing trend. In general, the particle size of the debris tends to decrease as the UV light exposure time elapses.
[0399] On the other hand, the polishing pad according to Comparative Example B1 showed a tendency that the chip particle size generally increased with the lapse of ultraviolet light irradiation time. It was measured that the chip particle size measured after 10 minutes was almost doubled compared to the initial stage.
[0400] Test Example B3: Performance Evaluation of Polishing Pad (CMP and UV Irradiation)
[0401] like Figure 7 and Figure 8 As shown, an angle and height adjustable ultraviolet lamp (700) is installed in a CMP polishing machine. A silicon wafer with a diameter of 300 mm on which silicon oxide has been deposited by a CVD process is placed on a porous polyurethane polishing pad installed on a chassis in the CMP polishing machine, with the silicon oxide layer of the silicon wafer facing downward. Then, the silicon oxide layer is polished under a polishing load of 4.0 psi, while the polishing pad is rotated at a speed of 150 rpm, a calcined cerium oxide slurry is supplied to the polishing pad at a rate of 250 ml / min, and a pressure plate is placed on the polishing pad. Rotate at a speed of 150 rpm for 60 seconds. During CMP polishing, the ultraviolet lamp (700) is started, and the polishing layer surface of the polishing pad is irradiated with ultraviolet light (wavelength 100 to 380 nm) at an intensity of 1 kW from a distance of 5 cm.
[0402] (1) Polishing speed (removal rate)
[0403] Similar to the above, after polishing, the silicon wafer was separated from the carrier, mounted in a spin dryer, rinsed with deionized water (DIW), and then dried with nitrogen for 15 seconds. The film thickness of the dried silicon wafer before and after polishing was measured using a spectroscopic reflectometer thickness gauge (manufacturer: Keyence, model: SI-F80R).
[0404] Thereafter, the polishing speed is calculated using the following Mathematical Formula 1.
[0405] [Mathematical formula 1]
[0406]
[0407] (2) Defects
[0408] Polishing was performed using a CMP polisher in the same manner as in the polishing speed test. After polishing, the silicon wafer was transferred to a cleaner and cleaned using 1% HF, 1% H 2 NO 3 The wafer was cleaned with 1% DIW and 1% DIW for 10 seconds each. Thereafter, it was transferred to a spin dryer, washed with DIW, and then dried with nitrogen for 15 seconds. The defect change of the dried silicon wafer before and after polishing was measured using a defect measurement device (manufacturer: Tenkor, model: XP+). Specifically, the total number of scratches, vibration marks, pits, and residues on the wafer surface was measured.
[0409] (3) Pad wear rate (PWR)
[0410] Each polishing pad was preconditioned with deionized water for 10 minutes at the initial stage, and then conditioned for 1 hour while spraying deionized water. In this case, the change in thickness was measured during the 1-hour conditioning. The conditioning equipment used was AP-300HM from CTS. The conditioning load was 6 lbf, the rotation speed was 100 to 110 rpm, and the disc used for conditioning was CI-45 from Sasol.
[0411] [Table 8]
[0412]
[0413] As a result of the test, the polishing pad of the example has a polishing speed and a pad wear rate within the desired range and has very few defects. Meanwhile, the polishing speed of the polishing pad of the comparative example is outside the desired range and the generation of defects increases.
[0414] [reference numerals]
[0415] 100: Polishing pad
[0416] 150: Debris
[0417] 200: Pressure plate
[0418] 300: Finisher
[0419] 400: Slurry supply device
[0420] 450: Polishing slurry (CMP slurry)
[0421] 510: Polishing head
[0422] 520: Carrier
[0423] 600: Semiconductor substrate (wafer)
[0424] 650: Defects
[0425] 700: UV lamp
[0426] 750: Ultraviolet light
Claims
1. A polishing pad, characterized in that: It includes a polishing layer, which includes a polyurethane-based prepolymer, a foaming agent and a curing agent; under the conditions of a platen speed of 93 rpm, a dresser load of 9 lbs, a dresser speed of 64 rpm, and a scanning speed of 19 times / minute, the polishing layer is dressed for 10 minutes, and deionized water is provided at a speed of 300 cc / minute, and the obtained debris D50 particle size is less than 50 μm and the pH is 5.5; when the pH is 5.5, the potential difference of the aqueous solution containing 0.01% by weight of the debris is -20 mv to 30 mv.
2. The polishing pad according to claim 1, wherein The D50 particle size of the chips obtained during the conditioning of the polishing layer was below 25 μm at a pH of 5.5 and below 22.3 μm at a pH of 10.
3. The polishing pad according to claim 1, wherein The potential difference of an aqueous solution containing 0.01% by weight of chips obtained when the polishing layer was conditioned for 10 minutes was -50 mv to -10 mv at pH 10.
4. The polishing pad according to claim 1, wherein When the polishing pad is used to polish the silicon oxide layer of a silicon wafer with ceria slurry, the polishing speed is as follows: to [Mathematical formula 1] 5. A polishing pad comprising a polishing layer containing a polyurethane resin, characterized in that: When the polishing layer was conditioned with a cerium oxide slurry at a rate of 250 ml / min under the conditions of a platen speed of 93 rpm, a dresser load of 9 lbs, a dresser speed of 64 rpm and a scanning speed of 19 times / min, and then irradiated with ultraviolet light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, the obtained chips satisfied the following relationship (1): D50 [0 min] > D50 [4 min] ... (1) Wherein D50[0min] is the D50 particle size of the chips obtained in the conditioning before irradiation with ultraviolet light, and D50[4min] is the D50 particle size of the chips obtained after irradiation with ultraviolet light for 4 minutes.
6. The polishing pad according to claim 5, characterized in that The ΔD50[0-4min] calculated according to the following formula is above 10 μm: ΔD50[0-4min]=D50[0min]–D50[4min] Wherein D50[0min] is the D50 particle size of the chips obtained in the conditioning before irradiation with ultraviolet light, and D50[4min] is the D50 particle size of the chips obtained after irradiation with ultraviolet light for 4 minutes.
7. The polishing pad according to claim 5, wherein: D50[4min] is less than 30μm.
8. The polishing pad according to claim 5, wherein: When the polishing pad is tested at a dressing pressure of 6 lbf and a rotation speed of 100 to 110 rpm, the pad wear rate (PWR) is 15 μm / hr to 40 μm / hr.
9. A method for preparing a semiconductor device, characterized in that: It includes polishing a surface of a semiconductor substrate using the polishing pad as claimed in claim 1 .
10. A method for preparing a semiconductor device, characterized in that: The method comprises irradiating a polishing layer of a polishing pad with ultraviolet light having a wavelength of 100 nm to 380 nm, and chemically and mechanically polishing a semiconductor substrate using the polishing pad as claimed in claim 5 .